2018
DOI: 10.1177/0033688218755847
|View full text |Cite
|
Sign up to set email alerts
|

Interculturality in the Language Class – Teachers’ Intercultural Practices in Ecuador

Abstract: The purpose of this study is to identify how Ecuadorian university teachers of English as a foreign language (EFL) tackle intercultural teaching practice in their classrooms. To this end, we studied the reported intercultural practices of 68 EFL university teachers from Ecuadorian Region 4. Quantitative data drawn from a questionnaire were analysed through descriptive statistics. The results suggest that the activities put into practice emphasize the development of intercultural attitudes rather than knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
2
10
0
2
Order By: Relevance
“…Without them he is nothing. As such, it mirrors previous study highlighting a strategy management of keeping distance between the speaker and the audience (Bu et al, 2020;Fernández-agüero & Chancay-cedeño, 2019;Qian & Pan, 2019). Saying it differently, the use of "we" in this speech tends to show that the speaker did not separate himself from the audience and did not put himself as the only agent of change.…”
Section: Will Work As Hard For Those Who Didn't Vote Me and Who Didsupporting
confidence: 82%
“…Without them he is nothing. As such, it mirrors previous study highlighting a strategy management of keeping distance between the speaker and the audience (Bu et al, 2020;Fernández-agüero & Chancay-cedeño, 2019;Qian & Pan, 2019). Saying it differently, the use of "we" in this speech tends to show that the speaker did not separate himself from the audience and did not put himself as the only agent of change.…”
Section: Will Work As Hard For Those Who Didn't Vote Me and Who Didsupporting
confidence: 82%
“…There are massive cases where the application of Intercultural Communication Competence in language learning & teaching already focuses on the third component: attitudes, and no longer limited to knowledge component and skills component. Unfortunately, most of the language teachers are focusing heavily on the culture of target country language but their own country culture receives little attention [13]. In this factor, language teacher plays a crucial role not only in the aspect of language teaching methodology but correspondingly to encourage learners in identifying personal self-identity linked to the critical cultural awareness component as mentioned in the model of Intercultural Communication Competence above [14].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies show that culture-based materials can improve students' speaking skills (Fernández-Agüero & Chancay-Cedeño, 2019;Aprianoto & Haerazi, 2019), reading skills (Hoff, 2019), and writing skills (Haerazi et al, 2018). Also, providing students with cultural activities can evolve students' cultural and intercultural awareness (McConachy, 2018;Kusumaningputri & Widodo, 2018), multicultural insight (Uzum et al, 2018), and linguistic awareness (Krulatz et al, 2018).…”
Section: Research Question 1: the Effectiveness Of The C-bim Modelmentioning
confidence: 99%
“…Afterward, students are asked to identify the values that are perceived by English-speaking people in pairs and individual activities. Some studies showed these learning activities were capable of developing intercultural competencies (Tambyah, 2018;Fernández-Agüero & Chancay-Cedeño, 2019;and Hagar & Hagar, 2018).…”
Section: Skills Of Interpreting and Relatingmentioning
confidence: 99%